2005
DOI: 10.1159/000086563
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial Arterial Ischemic Stroke following Cerebellar Tumor Resection in Two Children

Abstract: We describe two children who developed ischemic strokes in the territory of the middle cerebral artery, one 7 days and one 11 days after resection of a cerebellar tumor. In the first child, another infarction occurred in the territory of the contralateral middle cerebral artery 5 days after the first stroke. No specific cause or underlying risk factor other than the surgical procedure was found. The subacute clinical course at stroke onset resembled that of the ‘posterior fossa syndrome’, suggesting a common u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Anatomy: Most investigators agree that the basic cause of cerebellar mutism is bilateral interruption of the dentato-thalamocortical pathways (12,14,19,20,21,22,23,24,25). The most common explanation of cerebellar mutism emphasizes bilateral damage to the dentate nuclei (7,15,24,26).…”
Section: Clinical Findings and Incidencementioning
confidence: 99%
“…Anatomy: Most investigators agree that the basic cause of cerebellar mutism is bilateral interruption of the dentato-thalamocortical pathways (12,14,19,20,21,22,23,24,25). The most common explanation of cerebellar mutism emphasizes bilateral damage to the dentate nuclei (7,15,24,26).…”
Section: Clinical Findings and Incidencementioning
confidence: 99%
“…Imaging studies, i.e. single-photon emission computerized tomography (SPECT), dynamic susceptibility contrast (DSC) and arterial spin labelling (ASL) MRI studies, claim to have demonstrated the occurrence of cerebral hypoperfusion and cerebral metabolic hypofunction in paediatric patients who developed ppCMS after posterior fossa surgery [16][17][18]. However, these studies are frequently case reports or small case series.…”
Section: Introductionmentioning
confidence: 99%
“…En el mutismo cerebeloso y en el síndrome de mutismo cerebeloso el sustrato anatómico más citado en la literatura tiene relación con el núcleo dentado y el tracto dento-rubro-talámico [17][18][19][20][21][22][23] .…”
Section: Introductionunclassified